PREVALENSI, FAKTOR RISIKO DAN ANALISIS KERUGIAN NILAI EKONOMI MASTITIS OLEH Staphylococcus aureus PADA SUSU DI EKS KARESIDENAN MADIUN - , Supriyanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mastitis is an inflammation of the udder in the form of subclinical mastitis (MSK) and clinical mastitis (CM). Staphylococcus aureus is one of the main causes which can lead to loss of a drop in milk production. This study aims to determine the prevalence, risk factors, and the analysis of the loss of economic value of mastitis by S. aureus. An observational study with cross-sectional design was conducted on 226 dairy cow milk samples taken from 101 farmers in Ex residency of Madiun (Pacitan, Ponorogo, and Madiun). Methods of Taking in Sample was done by multiple stages sampling method and the proportional population of lactating dairy cows. Random sampling was done based on the highest until the lowest sequently in the district, sub-district, village and dairy farmers but the cattle taken in a cluster. To Determine of MSK by using California mastitis test (CMT), observation and palpation of the udder to the MK, and Isolation and identification of S. aureus using bacterial growth media and biochemical tests (mannitol salt Agar : MSA and Voges proskaeur: VP). The data Collected based on questionnaire and interviews with farmers, then analyzed by univariate, bivariate and multivariate (logistic regression and linear regression) using the software Statistix for Windows Version 7 (P <0.05). The results showed that: 1) the prevalence of MSK, MK and normal values respectively are 72.57%, 5.31% and 22.12%. 2) The prevalence of S. aureus in milk positive for 52.8% (8.41% of normal milk, MSK 40.41%, and 3.98% MK). 3) Factors that influence the incidence of mastitis in logistic regression are the cement floor of the cage, udder blisters, not use antibiotics, dirty water, farmerâs experience less than two years, the years of lactation, the not discard the first of milk secretion, and the months of lactation. 4) Factors that influence milk production are the height of the farm, months of lactation, age, not dyed nipples, mastitis, cow from outside, S. aureus positive, and once daily milking. 5) The loss of economic value by decreasing in milk production due to MSD at 6.09% - 21.88% (average 13.99%), MSK by S. aureus is 14.06% - 39.18% (average of 26.62%), MK and MK by S. aureus can respectively reach 100%. The conclusion is that mastitis in dairy cows have the risk of causing a loss of economic value greater than healthy cows. It could be severe by the presence of S. aureus and other risk factors so it needs the prevention, the control and the eradication of mastitis.